Increased numbers of P63-positive/CD117-positive cells in advanced adenoid cystic carcinoma give a poorer prognosis - Zhou Quan; Chang Hong; Zhang Hongkai; Han Yiding; Liu Honggang (BMC, 2012)
Abstract Objectives This study consisted of two parts. One part was to analyze the survival rates of adenoid cystic carcinoma (ACC) in Chinese and explain the difference between our data and the literature. The other was to analyze the relationship between the expression of CD117 and the histological grade and the prognosis. Methods A retrospective study of 80 ACC patients was performed. Clinical data were collected, and p63, CD117 were detected by immunohistochemical staining. Results Eighty patients received follow-ups 3 to 216 months after initial diagnosis. ACC occurred in the lacrimal gland (26.3%, n = 21), nasal cavity and parasinus (33.8%, n = 27) and other sites (40.0%, n = 33). The 5-year and 10-year survival rates were 66.41% and 10.16%, respectively. Over expression of CD117 was detected in p63-negative cells in 94.3% of cases and in p63-positive cells in 45.8%. The expression of CD117 in p63-positive cells was significantly associated with the histological grade (P<0.001) and prognosis (P = 0.037) in patients in the advanced stage. Conclusions ACC had a good 5-year survival but poor 10-year survival in Chinese, which differed from the occidental data. More p63+/CD117+ cells were associated with a higher histological grade and poorer outcome. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1701457278762097